2016
DOI: 10.1538/expanim.16-0033
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy combined with an engineered <i>Salmonella typhimurium</i> inhibits tumor growth in a mouse model of colon cancer

Abstract: The engineered Salmonella typhimurium ΔppGpp (S.t ΔppGpp) has been studied in terms of its ability to carry imaging probes (bacterial luciferase, Lux) for tumor imaging or carry therapeutic molecules (Cytolysin A) to kill cancer cells. To establish a novel cancer therapy, bacterial therapy was combined with radiotherapy using the attenuated strain S.t ΔppGpp/pBAD-ClyA. Radiotherapy (21Gy) contributed to S. typhimurium colonization in a colon tumor (CT26) model of BALB/c mice. The combination of bacterial thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 15 publications
0
37
0
Order By: Relevance
“…Because multiple bacteria strains expressing different therapeutics will compete for resources within a tumor, reducing the effective dosage of each therapeutic, the BSCC system can assess how combination therapy will perform when increasing the number of bacterial therapies. In addition, the broad applicability of the spheroid model can be employed to assess combinations of bacterial therapy with chemotherapy (42) and radiotherapy (43) to improve on existing treatments. The BSCC system is precisely suited to quantitatively explore large libraries and combinatorial strategies in a high-throughput fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Because multiple bacteria strains expressing different therapeutics will compete for resources within a tumor, reducing the effective dosage of each therapeutic, the BSCC system can assess how combination therapy will perform when increasing the number of bacterial therapies. In addition, the broad applicability of the spheroid model can be employed to assess combinations of bacterial therapy with chemotherapy (42) and radiotherapy (43) to improve on existing treatments. The BSCC system is precisely suited to quantitatively explore large libraries and combinatorial strategies in a high-throughput fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of studies have developed a new approach for cancer therapy using genetically engineered bacteria designed to express reporter genes, cytotoxic protein and/or anticancer agents, and tumor‐specific antigens . It has been found that genetically modified bacteria can have a more significant multiplication in tumors than in normal tissues . The ability of Salmonella typhimurium serovar VNP20009 and Clostridium butyricum M55 to selectively colonize tumors has allowed them to be used as delivery vectors in mouse tumor models, without severe immune responses or toxic side effects.…”
Section: Genetically Modified Bacteria In Cancer Therapymentioning
confidence: 99%
“…A serious drawback of radiotherapy is that it is not clear whether the radiation affects cytotoxin‐expressing Salmonella that has localized in the tumor. Liu et al reported that the combination of radiotherapy and bacterial therapy using engineered S typhimurium ∆ppGpp reduced tumor growth compared with bacterial therapy alone. In addition, the researchers recently showed that the agonist of toll‐like receptor 5 (TLR5), called bacterial flagellin, as well as CBLB502 (its pharmacologically optimized derivative) could protect primates and rodents from gastrointestinal and hematopoietic radiation syndromes induced by total body irradiation .…”
Section: Combination Of Bacteriotherapy With Radiotherapymentioning
confidence: 99%
“…Cytolysins are generally derived from Escherichia coli or Staphylococcus aureus [ 4 ]. Studies have demonstrated that mice on treating with S. typhimurium or E. coli strains expressing the ClyA toxin demonstrated tumor growth inhibition [ 11 , 17 ]. Jiang et al engineered cytolysin producing E. coli strain K-12 which in combination with radiotherapy retarded tumor growth in mice with tumors derived from murine CT26 colon cancer and prevented its metastatic spread [ 11 ].…”
Section: Mechanism Of Tumor Suppressionmentioning
confidence: 99%